LE TRAITEMENT NEUROCHIRURGICAL DE L'EPILEPSIE TEMPORALE PHARMACO-RESISTANTE - BENHMIDA KAWTAR (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2022)
The aim of our study is to analyze the impact of refractory epilepsy surgery on the prognosis of epilepsy in TLE patients of a series of 100 patients who underwent surgery at department the 'Hôpital des Spécialités- Rabat 'over a period of 15 years (2005-2020). The mean age at surgery is 26.3 years. The most affected age group is that between 20 and 29 with no significant predominance (F:51/M:49). The mean age at onset of epilepsy was 11,6 years and the median duration of epilepsy at the time of the surgery was 14,6 years. Type of epilepsy was focal in 24% combined (F+G) in 27% and generalized in 23%. 65.9% presented an automatism. The seizure frequency was weekly in 39.8%. The patients were treated with 2.34'{D8}+'0.837 AEDs. Presurgical assessment revealed: ' Video EEG finding were focal in 91.6%. PET scan: hypometabolism in 2 patients. ' MRI: SH (48%), DNET (19%), Glioma (9%), FCD (6%), undefined lesional abnormalities (15%), cavernoma (3%). The surgery type was TL in 88% (L:45; R:43) and lesionectomy in 12%(L:5 ; R:7). The histopathologic examination revealed: HS (40%), DNET (21%), oligodendroglioma (13%), dysplasia (7%), cavernoma (3%) and (1%) astrocytoma. The rate of minor complication was 25 % and the rate of post-operative mortality was zero. Engel's classification at the last follow up (2-11 years) was favourable in 80% (Engel I). Only one patient was Engel IV (DNET) and died from a SUDEP one year post surgery. A significant reduction in AEDs was noticed from (2.34'{D8}+'0.837 SD AEDs) before the surgery to (1.93 {D8}+'0.959 SD; p: 0.029), 7.3% were free from AED at the last follow up. The results of our study are encouraging despite the use of only non-invasive methods. Surgery remains better than prolonged medical treatment in adult patients with drug refractory temporal lobe epilepsy.
Keywords: Refractory epilepsy; temporal lobe epilepsy; surgery; prognosis; Engel; Refractory epilepsy; Temporal lobe epilepsy; Surgery; Prognosis; Engel 9